"The Achilles of Sunday": William Sherman's Redemption at Shiloh - Hotz, Robbie (Kansas State University. Dept. of History, 2012)
When people think of Willam Tecumseh Sherman they often imagine the hard and tough general who burned Atlanta and devastated the Confederacy in his march to the sea. However, few are aware of his nervous breakdown early in the war which could have removed him from the conflict entirely. This study examines the reasons why his nervous breakdown occurred and how he redeemed himself at the Battle of Shiloh just a few months later. In it I argue that William Tecumseh Sherman’s performance in the Battle of Shiloh was part of his deliberate plan to restore his self-confidence and personal honor, and that he was successful in regaining both. Through the analysis of letters, books, newspapers, and other sources I have discovered that Shiloh was indeed a redemptive experience for Sherman. Therefore, this study offers a new perspective on one of the civil war’s most influential and impactful soldiers, who nearly missed becoming one of America’s great historical figures.
Keywords: Sherman; Civil War